Ketuban Pecah Dini di Rumah Sakit Umum Daerah Ungaran - Rohmawati, Nur; Wijayanti, Yuni (HIGEIA (Journal of Public Health Research and Development), 2018)
Abstrak Ketuban pecah dini (KPD) adalah pecahnya selaput ketuban sebelum waktunya melahirkan. Pada tahun 2017 Jumlah kasus ketuban pecah dini di RSUD Tugurejo merupakan salah satu jumlah kasus tertinggi (43,1%) dibandingkan dengan jumlah kasus komplikasi persalinan lainnya seperti pendarahan anterpartum, postpartum, pre-eklamsia berat, dan preeklamsia.  Jenis penelitian ini adalah observasional analitik dengan rancangan case-control. Sampel yang ditetapkan sebesar 46 kasus dan 46 kontrol dengan teknik purposive sampling. Data dianalisis dengan menggunakan uji chi-square. Hasil menunjukkan ada hubungan antara malposisi (malpresentasi) janin (p value = 0,019), umur ibu (p value = 0,033), paritas (p value = 0,003), riwayat KPD (p value = 0,005), status pekerjaan ibu (p value = 0,019), status anemia (p value = 0,010), paparan asap dan perilaku merokok ibu (p value = 0,004)dengan kejadian ketuban pecah dini. Tidak ada hubungan antara kehamilan kembar (ganda) (p value = 0,31), riwayat keturunan (p value = 0,315), riwayat keguguran berulang dengan kejadian ketuban pecah dini (p value = 0,358). Abstract Early rupture of membranes was the rupture of the membranes prematurely before delivery. In 2017, the number of case membrane broke early in the hospital of Tugurejo is one of the number of cases highest compared (43,1%) with the others of the number of complication cases such as anter-partum. The type of research is analytic observational with case-control design. Sample that is set of 46 cases and 46 controls with the technique of purposive sampling.The data of analysis is chi-squre test. The result of research show there is relation between mal-position/mal-presentation of embryo (p value=0,019), age of mother (p value= 0,033), parity (p value= 0,003), the history of KPD (p value= 0,005), the status of mother employment (p value= 0,019), the status of anemia (p value= 0,10), smoking exposure and behavior smoking of mother (p value= 0,004) with membrane broke early. There is not relation between history of the descendant (p value= 0,315), history of recurrent miscarriage (p value= 0,94), and twin pregnancy (gamelly) (p value= 0,358). Keyword : Complication, Membranes, broke early